PROSPEK USAHA PENGOLAHAN UDANG REBON SKALA RUMAH TANGGA DI DESA MUARA KINTAP KECAMATAN KINTAP KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Syahrin, Alfi; Mahyudin, Idiannor; Mahreda, Emmy Sri (EnviroScienteae, 2016)
The problems in rebon shrimp processing business at household scale in Desa Muara Kintap  are in processing, utilization, and improvement in processing business which have not been maximized, and rebon shrimp quality of the business community at household scale because of inappropriate processing and handling, lack of interest, and cheap selling price. To overcome these problems, one possible way is to provide proper handling to the products of rebon shrimp either in producing or packaging as well as diversifying the processing of rebon shrimp. Therefore, this study aims to (1) determine benefits, eligibility, fluctuation and variation in price and (2) analyze marketing channels of rebon shrimp in Desa Muara Kintap. The significance of this research is that it can be used as an input or a reference in order to increase profits and development of business prospect of rebon shrimp processing at household scale in Desa Muara Kintap,Kecamatan Kintap,Kabupaten Tanah Laut, South Kalimantan Province; and it is also useful for those who want to learn more about the development of business prospect of rebon shrimp processing at household scale in Desa Muara Kintap,Kecamatan Kintap,Kabupaten Tanah Laut, or for those who are interested in the issues in this study. The results showed that the processing business of dried rebon shrimp in Muara Kintap was profitable to do because the total revenue was greater than the total cost, and based on the analysis of the eligibility on the season of NPV, Net BCR, and IRR were on top of the value of 13%, making it eligible to do business processing, and there was also a price fluctuation with an average selling price fluctuation of rebon shrimp in Desa Muara Kintap  between ‘season’ and ‘not season' the prices was 41.05%, and the variation of the fishing season prices ranged from Rp 19,000 to Rp 20,000, while during ‘not season’ the prices were between Rp 26,000 and Rp 30,000. This happened because of the difference in total costs incurred by the fishermen and rebon shrimp processors and the difference in rebon shrimp production volume, and there were two marketing channels of rebon shrimps in Desa Muara Kintap.